Physical therapists' self-perceived adequacy of entry-level education and their current confidence levels with respect to temporomandibular disorders: A pilot study. Issue 5 (2nd September 2020) - Gadotti, Inae C.; Lakow, Alixandra; Cheung, Jocelyn; Tang, Michael
ABSTRACT: Objective: Physical therapy (PT) has been shown to be one of the most effective conservative treatments for temporomandibular disorders (TMD). The objectives of this pilot study are to determine the self-perceived knowledge, adequacy of entry-level education, and the current confidence levels of PTs in Florida regarding TMD treatment. Methods: An online questionnaire was used. The overall experience, education, and confidence regarding TMD treatment and its implications were discussed. Results: A total of 247 PTs participated. Nearly 70% of the PTs responded that they did not believe they received adequate education in TMD, and 50% are not confident to treat these patients. Seventy-seven percent were interested in knowing more about PT for TMD. Discussion: This pilot study shows the lack of confidence of PTs in Florida to treat TMD patients. More adequate training on TMD in the entry-level professional education is needed.